2007
DOI: 10.1186/1472-6963-7-72
|View full text |Cite
|
Sign up to set email alerts
|

Access to electronic health knowledge in five countries in Africa: a descriptive study

Abstract: Background: Access to medical literature in developing countries is helped by open access publishing and initiatives to allow free access to subscription only journals. The effectiveness of these initiatives in Africa has not been assessed. This study describes awareness, reported use and factors influencing use of on-line medical literature via free access initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 5 publications
7
60
0
Order By: Relevance
“…[57][58][59] Indeed, most publishers participate in several programs simultaneously. 60 In addition, researchers may find informal avenues of access to the journal literature, such as requesting copies of articles from the author or from peers at other institutions, 32,61 and by relying on freely accessible copies of articles self-archived in digital repositories. 62,63 Alternate avenues of access may make it more difficult to isolate the effect of TEEAL specifically on citation behavior.…”
Section: Other Avenues Of Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…[57][58][59] Indeed, most publishers participate in several programs simultaneously. 60 In addition, researchers may find informal avenues of access to the journal literature, such as requesting copies of articles from the author or from peers at other institutions, 32,61 and by relying on freely accessible copies of articles self-archived in digital repositories. 62,63 Alternate avenues of access may make it more difficult to isolate the effect of TEEAL specifically on citation behavior.…”
Section: Other Avenues Of Accessmentioning
confidence: 99%
“…23,64 In a related study of the use of HINARI, doctors and researchers expressed frustration with retrieving login passwords from their librarians who served often as gatekeepers to online journals. 61 …”
Section: Access To Teeal At Subscribing Institutionsmentioning
confidence: 99%
“…A more recent survey showed that for medical postgraduate trainees in Africa, the sources of health information accessed were textbooks (70%), e-resources (29%) and paper journals (1%). The source of web access was web cafes (up to 90%) or institutional libraries (up to 78%) depending on the country, with access from home contributing a sizable minority (up to 24%) [13].…”
Section: Access To the Literaturementioning
confidence: 99%
“…on awareness of online disseminated literature and on good technical facilities (cf. slow Internet connections, unreliable power supplies, and even free password assignment from librarians), as recently shown by Smith et al (2007). The digital divide (Carthage Declaration, 2005;Sciadas, 2005) may thus remain an obstacle to the reduction of the scientific divide.…”
mentioning
confidence: 99%